ANALISIS PENGARUH PROFITABILITAS, EFEKTIVITAS, DAN STRUKTUR MODAL TERHADAP KEKURANGAN KEUANGAN PADA SEKTOR INFRASTRUKTUR, UTILITAS, DAN TRANSPORTASI PADA PERIODE 2018—2020 - primaria tinutomo; Julianti Sjarief (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2023)
This study aims to analyze the influences of Net Profit Margin, Total Asset Turnover, and Debt-to-Equity Ratio on Financial Distress in Infrastucture, utility and transportation sector in the period 2018 to 2020. The sample selection used the purposive sampling method with sample size of 101. The analytical method used in this study is the descriptive analysis method and multiple linear regression analysis, where the data is processed using the Statistical Package for the Social Sciences version 25 program. The results of this study are Net Profit Margin and Total Asset Turnover to have negative effects on Financial Distress while Debt-to-Equity Ratio has positive effects on Financial Distress.